Systemic lupus erythematosus - Mackillop, Lucy H; Germain, Sarah J; Nelson-Piercy, Catherine (BMJ, 2007)
Systemic lupus erythematosus (SLE) is a multisystem relapsing and remitting autoimmune disease. The management of this condition in pregnancy provides the obstetrician, physician, and general practitioner with particular challenges and concerns related to the mother and her baby. Here, Mackillop et al discuss these challenges and talks about how pregnancy affect SLE and vice versa. Moreover, they conclude that SLE and the overlap condition of the antiphospholipid syndrome present several challenges in managing a pregnant woman and her fetus. A successful pregnancy outcome depends on stratification of risk at the outset (ideally before pregnancy) and careful and appropriate monitoring during the pregnancy. Should the disease flare up, aggressive but considered management is advocated to reduce maternal and fetal morbidity.